2016
DOI: 10.1521/pedi_2015_29_213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Personality Disorders on Self-Other Agreement and Favorableness in Personality Descriptions

Abstract: The authors studied effects of self-reported personality disorder (PD) symptoms on interpersonal perception, particularly self-other agreement and favorableness. Using a round-robin design, 52 groups of four well-acquainted students described themselves and each other on a measure of the Five-Factor model of personality and were administered a self-report screening instrument for DSM-IV (Axis 2). Using the Social Accuracy Model, the peer reports were predicted, across items, from either (a) the target person's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…While the Dark Tetrad traits were largely related to negative evaluations—viewing qualities of the interaction and interaction partner negatively—these associations were not as robust or consistent for narcissism. These findings are largely in line with research on subclinical narcissism and perceptions of others (Rauthmann, ), but in contrast with previous research linking narcissistic personality disorder to the formation of particularly negative impressions of others (Tandler, Mosch, Wolf, & Borkenau, ). Thus, there is something unique about subclinical narcissism that is not quite as negative as the other Dark Tetrad traits, and that differs from the perceptual patterns linked to clinical levels of narcissism.…”
Section: Discussionsupporting
confidence: 88%
“…While the Dark Tetrad traits were largely related to negative evaluations—viewing qualities of the interaction and interaction partner negatively—these associations were not as robust or consistent for narcissism. These findings are largely in line with research on subclinical narcissism and perceptions of others (Rauthmann, ), but in contrast with previous research linking narcissistic personality disorder to the formation of particularly negative impressions of others (Tandler, Mosch, Wolf, & Borkenau, ). Thus, there is something unique about subclinical narcissism that is not quite as negative as the other Dark Tetrad traits, and that differs from the perceptual patterns linked to clinical levels of narcissism.…”
Section: Discussionsupporting
confidence: 88%
“… 2. Other findings from this research project, some of them relying on measures not described here, are reported by Borkenau, Mosch, Tandler, and Wolf (2016) and by Tandler, Mosch, Wolf, and Borkenau (in press). …”
mentioning
confidence: 60%
“…Persons showing symptoms of maladjustment are likely to receive more negative feedback from others, sensitizing them that their perceptions by others tend to be inconsistent with their self-concept. Indeed, high PD scores are associated with less self–other agreement in ratings of personality (Tandler, Mosch, Wolf, & Borkenau, in press). And the effect may also take the opposite direction: Persons who realize that others perceive them differently from how they perceive themselves may feel misunderstood, disoriented, or treated unfairly, resulting in PD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of results could not have been established using an item-wise approach. Fourth, there is evidence that targets who report better psychological adjustment show higher distinctive self-other agreement (Human & Biesanz, 2011a; Tandler, Mosch, Wolf, & Borkenau, 2015). A possible explanation for this effect is that targets who are better psychologically adjusted provide others with more valid cues to their own more private experiences (Human, Biesanz, Finseth, Pierce, & Le, 2014).…”
Section: Findings Concerning Distinctive Profilesmentioning
confidence: 99%
“…Profile analysis is the ideal method of approaching this question because it enables comparisons among individual perceivers in terms of the average accuracy of their judgments across a broad range of traits. Surprisingly, the search for attributes of good judges of personality has failed to yield replicable results: Whereas informants tend to be generally aware of targets’ distinctive personality features, they seem not to differ very much from each other in this respect (Biesanz, 2010; Tandler et al, 2015).…”
Section: Findings Concerning Distinctive Profilesmentioning
confidence: 99%